2013
DOI: 10.2967/jnumed.113.120493
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Epidermal Growth Factor Receptor Targeting Probe [11C]PD153035: Impact on Biodistribution and Tumor Uptake in Rats

Abstract: Several tracers have been evaluated as probes for noninvasive epidermal growth factor receptor (EGFR) quantification with PET. One of the most promising candidates is the 11 C-labeled analog of the EGFR tyrosine kinase inhibitor PD153035. However, previous in vitro studies indicated extensive metabolism of the tracer, which could be disadvantageous for the assessment of receptor density in vivo. The aim of this study was to investigate the in vivo metabolism of [ 11 C]PD153035 to determine whether alterations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Previously, it was reported that PD153035 (N-(3-bromophenyl)-6,7-dimethoxyquinazolin-4-amine hydrochloride) is a very good molecular TKI for lung cancers, but has potent toxicity and no effects on lung cancer patients with mutated EGFR. 12,14 Thus, it is important to design and synthesize novel types of small molecule TKIs with lower liver toxicity but specifically binding with mutated EGFR.…”
mentioning
confidence: 99%
“…Previously, it was reported that PD153035 (N-(3-bromophenyl)-6,7-dimethoxyquinazolin-4-amine hydrochloride) is a very good molecular TKI for lung cancers, but has potent toxicity and no effects on lung cancer patients with mutated EGFR. 12,14 Thus, it is important to design and synthesize novel types of small molecule TKIs with lower liver toxicity but specifically binding with mutated EGFR.…”
mentioning
confidence: 99%
“…[43][44][45][46] In this study, Log P values of excreted through the hepatobiliary pathway, which is often observed for small molecule radiotracers directed to the ATP-binding site of TKs. 20,23,47,48 This excretion route may be due to the moderately high lipophilicities of these radiotracers.…”
Section: Discussionmentioning
confidence: 99%
“…Interventional techniques may be a useful tool to overcome this problem by selective administration of targeted nanoparticles under MRI [20, 21]. For studies requiring radiotracers that undergo an important first passage metabolism in, for example, the liver, this principle could be of utmost importance, as we have recently demonstrated using these techniques [22]. …”
Section: Discussionmentioning
confidence: 99%